Optimizing Palliative Management For End-of-Life Elderly Patient With Non-Hodgkin Lymphoma : A Case Report - Steven Jonathan; Devina Ravelia Tiffany Subroto; I Putu Bayu Triguna (International Journal of Health and Pharmaceutical (IJHP), 2026)
Diffuse Large B-Cell Lymphoma (DLBCL) is the most common type of non-Hodgkin’s lymphoma (NHL) in the elderly population. DLBCL is potentially curable with immunochemotherapy but becomes more difficult to cure as patients get older leading to poor prognosis. Palliative care is essential for patients with this condition to relieve their suffering and improve their quality of life. Treatment strategies of DLBCL in elderly patients remain a challenge for physicians and the patients. An 87-year-old male presented with difficulty swallowing for the past four months, worsened since last week. Throat pain, obstruction sensation, and confined to bed due to weakness. The patient has been diagnosed with DLBCL and refused chemotherapy. Dark-colored residue was observed in the nasogastric tube. There is an enlargement of right cervical lymph-node. His laboratory workup shows Hb 8,9mg/dL, histopathological of the oropharyngeal tissue showed Diffuse Large B-Cell Lymphoma, activated B-Cell subtype. Patient was treated through multidisciplinary approach to improve overall condition and his quality of life. The management of elderly patients with DLBCL requires multidisciplinary approach that considers patient preferences and quality of life. Elderly Prognostic Index are needed to evaluate patient condition, prognosis, and guide therapeutic decisions. Palliative therapy is an approach aimed at improving the quality of life of patients facing life-threatening illness through early identification and comprehensive management of pain, physical, psychosocial, and spiritual problems. Management of DLBCL in elderly patients requires balancing risks and benefits considering frailty, comorbidities, and overall functional status. Regardless of therapeutic choice, palliative and supportive care should be provided through a multidisciplinary approach to relieve suffering and preserve quality of life. Treatment decisions should be made involving the patient and their family, focusing on the ultimate goals of care in accordance to their wishes.